Toxicological Implications of Polluted Water from Makera Drain, Kaduna on Some Cereals and Horticultural Crop - Dadi-Mamud, N. J; Oniye, S.J2; Balarabe, M.L; Auta , J.; Gudugi, I.A.S (Mediterranean Journal of Social Sciences, 2012)
Concentrations of some heavy metals in crops such as banana, pawpaw, maize, sugarcane and mangoirrigated with water from Makera drain, Kaduna-Nigeria were investigated. These were determined byAtomic Absorption Spectrophotometer (AAS) technique. The metals were found to be in the magnitude ofZn> Pb> Cr >Cu, while that of the trace metals are Mg>Na>Ca in decreasing order of magnitude. Therewas varying level of significance (p<0.05) with increased concentrations of the determined metals. The highlead and chromium concentration (above WHO limit) in the irrigated crops may lead to its toxic effects asit can bio-accumulate in the tissues and muscles of human and domestic animals that utilize them as feed.It is thus observed that the water from the Makera drain used to irrigate crops may have delibetating effecton the consumers. Consumption of crops irrigated along the drain should be discouraged as it mightcontain high concentration of chromium and other toxic substances.